“Influencia de la dieta en la salud oral de estudiantes. Universidad Nacional de Chimborazo, 2019” - Gisela Isamar, Pesantez Chiriboga (2019)
This research project analyzed the influence of diet on the oral health in students at the National University of Chimborazo, 2019. This research was descriptive, in situ and cross-sectional. The population came from four majors, in Health Sciences College. It accounted for 1559 students in total. Its sample was 308 students through a simple random, and meeting a selection criteria. Two techniques were used such as a survey and an observation, all of them with their respective instruments. A questionnaire and its checklist were created by student. They were duly elaborated using the method of reliability and validation. The statistics results showed that the consumption of unhealthy foods neither affirms nor depicts a close relationship with plaque categories; that is to say, statistically, there are not significant differences. No alterations were found before the CPO index employment. There is not a direct link between either plaque absence or plaque presence with unhealthy food consumption. This is why, it can be concluded that, although the consumption of unhealthy food does not have a direct influence on the presence of oral pathologies, this type of food in combination with poor eating habits by the student population resulted in high levels of simplified oral hygiene index. Additionally, it demonstrates that diet alone is not an indicator of tooth cavity.